Non-oxidative ethanol metabolism in human hepatic cells in vitro: Involvement of uridine diphospho-glucuronosyltransferase 1A9 in ethylglucuronide production. (August 2020) - Hugbart, Chloé; Verres, Yann; Le Daré, Brendan; Bucher, Simon; Vène, Elise; Bodin, Aude; Lagente, Vincent; Fromenty, Bernard; Bouvet, Renaud; Morel, Isabelle; Loyer, Pascal; Gicquel, Thomas
Abstract: Ethanol is the most frequently psychoactive substance used in the world, leading to major public health problems with several millions of deaths attributed to alcohol consumption each year. Metabolism of ethanol occurs mainly in the liver via the predominant oxidative metabolism pathway involving phase I enzymes including alcohol dehydrogenases (ADH), cytochrome P450 (CYP) 2E1 and catalase. In a lesser extent, an alternative non-oxidative pathway also contributes to the metabolism of ethanol, which involves the uridine diphospho-glucuronosyltransferase (UGT) and sulfotransferase (SULT) phase II enzymes. Using liquid chromatography-high resolution mass spectrometry, ethylglucuronide (EtG) and ethylsulfate (EtS) produced respectively by UGT and SULT conjugation and detected in various biological samples are direct markers of alcohol consumption. We report herein the efficient non-oxidative metabolic pathway of ethanol in human differentiated HepaRG cells compared to primary human hepatocytes (HH). We showed dose- and time-dependent production of EtS and EtG after ethanol (25 or 50 mM) treatment in culture media of differentiated HepaRG cells and HH and a significant induction of CYP2E1 mRNA expression upon acute ethanol exposure in HepaRG cells. These differentiated hepatoma cells thus represent a suitable in vitro human liver cell model to explore ethanol metabolism and more particularly EtG and EtS production. In addition, using recombinant HepG2 cells expressing different UGT1A genes, we found that UGT1A9 was the major UGT involved in ethanol glucuronidation. Graphical abstract: Unlabelled Image Highlights: Ethylglucuronide (EtG) and Ethylsulfate (EtS) are two metabolites of ethanol used as direct markers of alcohol consumption. Using LC-HRMS, we report the dose- and time-dependent EtG and EtS production after ethanol treatment by human hepatocytes. Using recombinant HepG2 cells, we found that UGT1A9 was the major UGT involved in ethanol glucuronidation.